2012
DOI: 10.2478/s11535-012-0097-1
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of a doubled haploid winter wheat population under heat stress

Abstract: Breeding of new winter wheat cultivars with good heat tolerance requires better understanding of the genetic background of heat tolerance. In the present work the effect of heat stress on the 6 th day after heading was investigated in a doubled haploid (DH) population arising from a cross between heat-sensitive (Plainsman V) and heat-tolerant (Mv Magma) cultivars. Averaged over the population, heat stress was found to result in a significant reduction in biomass, grain yield and grain number per plant, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
4
1
Order By: Relevance
“…thermal and rainfall factors, influence crop plants growth and development, causing quantitative modifications of plants morphological structure, durations of developmental phases and yield-forming factors levels, which determine grain yield per spike and per plant are presented widely in literature (Gut et al, 1996;Kaur and Behl, 2010;Porter and Gawith, 1999;Barnabás et. al., 2008;Modarresi et al, 2010;Orzech et al, 2009;Rahman et al, 2009;Rajala et al, 2009;Spiertz et al, 2006;Ugarte et al, 2007;Balla et al, 2012, Golba et al, 2013, Talukder et al, 2013. Our results presented in this publication, concerning the impact of variable weather conditions on plant or spike morphological structure, yield-forming factors level as an equivalent to yield components and grain yield per spike and per plant, showed similarities with literature data presented above.…”
Section: Path Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…thermal and rainfall factors, influence crop plants growth and development, causing quantitative modifications of plants morphological structure, durations of developmental phases and yield-forming factors levels, which determine grain yield per spike and per plant are presented widely in literature (Gut et al, 1996;Kaur and Behl, 2010;Porter and Gawith, 1999;Barnabás et. al., 2008;Modarresi et al, 2010;Orzech et al, 2009;Rahman et al, 2009;Rajala et al, 2009;Spiertz et al, 2006;Ugarte et al, 2007;Balla et al, 2012, Golba et al, 2013, Talukder et al, 2013. Our results presented in this publication, concerning the impact of variable weather conditions on plant or spike morphological structure, yield-forming factors level as an equivalent to yield components and grain yield per spike and per plant, showed similarities with literature data presented above.…”
Section: Path Analysissupporting
confidence: 89%
“…Literature data indicates that temperature increase (heat stress) leads to reduction of grain yield resulting in a smaller number of individuals and different yield-forming factors taking into account by researchers (Balla et al, 2012;Rahman et al, 2009;Modarresi et al, 2010;Spiertz et al, 2006;Ugarte et al, 2007;Sharma et. al., 2008;Hossain et al, 2013, Talukder et al, 2013.…”
Section: Path Analysismentioning
confidence: 99%
“…In the present study, heat treatment was carried out at five different phenological phases, from the first node detectable (DEV31) growth stage to 20 days after flowering, on four wheat genotypes with very different adaptation strategies, representing the pair wise parental lines of two wheat mapping populations (Balla et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that high temperatures cause an array of morpho-anatomical, physiological, biochemical, molecular and cellular changes in plants (Wahid et al 2007;Barnabás et al 2008;Almeselmani et al 2012). There is increasing evidence on the significant negative effects of heat stress on yield and yield components during the generative phases (Farooq et al 2011;Semenov and Shewry 2011;Balla et al 2012). Elevated temperature induces pollen sterility and seed abortion, resulting in lower seed weight, and also significantly affects flour yield and dough quality (Hays et al 2007;Altenbach 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Budak et al (2013) agreed that utilization of drought tolerant wild species and the rapid advances in molecular, biological, functional genomics, and transgenic technologies have facilitated drought-related studies. However, using physiological screening and the measurement of yield components under stress condition is still the most effective way of identifying stress-tolerant wheat lines (Balla et al 2012). The most popular approach to breeding until now has been to select for plants with highest yield in field trials across the production zone (Tardieu and Hammer 2012).…”
Section: Introductionmentioning
confidence: 99%